The impulse factor : why some of us play it safe and others risk it all - Tasler, Nick, 1978- (Simon & Schuster, 2008)
Tasler teaches readers how to thrive when faced with difficult choices, provides a clear understanding of why you make the choices you do, and suggests the tools to make those decision change your business and your life.